THECAMOEBIANS (TESTACEOUS RHIZOPODS) FROM A TROPICAL LAKE: LA FE RESERVOIR, ANTIOQUIA, COLOMBIA - ESCOBAR JAIME; MARTÍNEZ JOSÉ IGNACIO; PARRA LUIS NORBERTO (Caldasia)
This research describes thecamoebians and explores their utility as environmental bioindicators on La Fe Reservoir, Antioquia, Colombia. Nineteen dredge samples were collected at the sediment-water interface, with a cylindrical dredge in March and October 2001. Temperature, pH, conductivity and total dissolved solids were recorded in situ both at depth and at surface for each sample locality. Counting of thecamoebians was done in the >63μm size fraction until 200 thecamoebians per sample were identified. A total of 6 genera, 14 species and 25 sub-species were found at La Fe Reservoir. Arcella vulgaris and Centropyxis aculeata dominate most of the samples. This study opens the possibility for additional research with thecamoebians as bioindicators of limnological physical parameters in tropical water bodies and calls for a further explanation for the occurrence of A. vulgaris and C. aculeata as the dominating species on this tropical reservoir.